(3eaJGM GdSYGOI, heUHGM GdSjGOIs - (3GdJQcj, CHh GdNjQ, WGTcHQj RGOg, YUGe GdOjf, CMeO Hf eUWai Hf Ndjd, (B968 (3g`s ((3eUWai GdbGVjs)
(3ChdgG (B:s
(3HSe Gddg HOjY HjGf dG jMJPi eKGdg agPg HK deG hbQ aj UOQj ef GdYdhe GdaGNQI hYjf HYO CKQ aj JMUjd SYGOI GdBNQI CedjJgG Hbde jHOA GdYLGH EPG SCd Ch CLGHs
(3BNQgG (B:s
(3hbO GYJfi GdYdeGA HTCf GdbVGA aChaQhG BOGH GdbVGA aj JUfja jSJbd hBTgQ GdJUGfja hPdc cJGH GdMcUGa hZjQ Pdc ef GdcJH GdeTghQI GdJj jYQagG CgdgG Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\257s
(3cTa GdXfhf (B2\1762s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdagGQS hGdecJHGJs